PERFORMANCE EXPECTANCY FACTORS AND OTHER FACTORS AFFECTING INTENTION TO RECOMMEND DANA APPLICATIONS IN TANGERANG DISTRICT - Dihin Septyanto; Silvia Angelita; Rojuaniah Rojuaniah; Ikramina Larasati Hazrati Havidz; Diana Fajarwati (SEAN Institute, 2023)
The purpose of this research is to know the factors affecting the intention to recommend Dana applications in the Tangerang district with the intention to adopt as an intervening variable. The population in this study are E-wallet users throughout Indonesia whose numbers are unknown. To determine the sample size, this study used purposive sampling so that 135 respondents were used as samples. Data analysis using SmartPLS version 3.0. There are several findings in this study, namely Performance Expectancy, Effort Expectancy, Hedonic Motivation, Lifestyle Compatibility, Perceived Trust, and Intention to Adopt Dana have a positive effect on Intention to Recommend Dana. Meanwhile, Social Influence and Facilitating Conditions have no significant effect on Intention to Recommend Dana.